1429. Real-World Study of Patients with Uncomplicated Urinary Tract Infection in the United States: High-Risk Comorbid Conditions and Burden of Illness. (4th December 2021) - Preib, Madison T; Marijam, Alen; Mitrani-Gold, Fanny S; Gibbons, Daniel C; Sun, Xiaoxi; Adams, Christopher; Joshi, Ashish V
Abstract: Background: Urinary tract infections (UTIs) are associated with significant morbidity and economic burden, particularly in the elderly and patients with comorbidities. We used real-world data (RWD) to assess healthcare resource use (HRU) and costs in patients with uncomplicated UTI (uUTI) and high-risk comorbid conditions in the US. Methods: This was a retrospective cohort study (IBM MarketScan RWD, commercial/Medicare Supplemental claims January 1, 2014–December 31, 2017) of females ≥ 12 years of age with uUTI who had an oral antibiotic prescription ± 5 days of uUTI diagnosis (index date) and continuous health-plan enrollment for ≥ 1 year pre-/post index date. Five high-risk cohorts and matched-control cohorts (baseline age, region) were identified: controlled type 2 diabetes (T2D), mild/moderate chronic kidney disease (CKD), recurrent UTI (rUTI), elderly (ELD), and postmenopausal (PMP) (Table 1 ). Sample sizes were balanced via random match selection (1:5 case:control). uUTI-related HRU and costs were compared between cases and controls (index episode/1-year follow-up) using multivariable generalized linear models. Table 1. Cohort assignment for high-risk cohorts and controls Results: Of 339, 100 patients with uUTI, case/control cohorts comprised T2D, n=15, 423/n=77, 115; CKD, n=1041/n=5205; rUTI, n=7937/n=39, 685; ELD, n=23, 666/n=118, 330; and PMP, n=105, 608/n=211, 216 patients. HRU trends across cohorts varied. During 1-year followup, outpatient visits were significantly different for cases versus controls in the T2D, rUTI, and PMP cohorts (p ≤ 0.0079), with higher case than control values in the rUTI and PMP cohorts; pharmacy claims were significantly higher for rUTI, ELD, and PMP cases, and inpatient visits were significantly higher for ELD and PMP cases, versus controls (all p < 0.0001; Table 2). Adjusted total uUTI-related costs (emergency room + outpatient + pharmacy) were significantly different (p < 0.0001) for cases versus controls at index episode and during follow-up in all cohorts except CKD: case values were higher than controls at index episode and during follow-up in the T2D cohort, and during follow-up in the rUTI and ELD cohorts (Table 3). Table 2. uUTI-related HRU* for cases versus controls according to high-risk cohort Table 3. uUTI-related costs* for cases versus controls according to high-risk cohort Conclusion: Females in some high-risk case cohorts had higher uUTI-related HRU and costs versus controls. Further studies of relationships between comorbidities and uUTI burden are needed. Disclosures: Madison T. Preib, MPH, STATinMED Research (Employee, Former employee of STATinMED Research, which received funding from GlaxoSmithKline plc. to conduct this study) Alen Marijam, MSc, GlaxoSmithKline plc. (Employee, Shareholder) Fanny S. Mitrani-Gold, MPH, GlaxoSmithKline plc. (Employee, Shareholder) Daniel C. Gibbons, PhD, GlaxoSmithKline plc. (Employee, Shareholder) Xiaoxi Sun, MA, STATinMED Research (Employee, Employee of STATinMED Research, which received funding from GlaxoSmithKline plc. to conduct this study) Christopher Adams, MPH, STATinMED Research (Employee, Employee of STATinMED Research, which received funding from GlaxoSmithKline plc. to conduct this study) Ashish V. Joshi, PhD, GlaxoSmithKline plc. (Employee, Shareholder)